2018
DOI: 10.1680/jsmic.19.00009
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and challenges of automated materials technology in industrial construction projects

Abstract: The widespread adoption of automated materials locating and tracking technologies (AMLTTs) in the construction supply chain can positively impact productivity in industrial construction projects. Prior academic studies have identified the need, recommended the use and demonstrated the potential of AMLTTs using field trials and experiments. These studies have also identified the potential benefits and challenges of AMLTT implementation. Very few studies have empirically examined the on-site application of AMLTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Similar technology combinations have also been used to improve the visibility of prefabricated materials in the storage sites at offsite fabrication yards (Ergen and Akinci, 2008). The information that is exchanged in electronic format includes information about "shipments, packing lists, inspections, purchase orders, fabrication progress, material receipts, material storage and location, material withdrawal requests, material pick and issue lists" (Dharmapalan and O'Brien, 2018).…”
Section: Information Sharing In Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar technology combinations have also been used to improve the visibility of prefabricated materials in the storage sites at offsite fabrication yards (Ergen and Akinci, 2008). The information that is exchanged in electronic format includes information about "shipments, packing lists, inspections, purchase orders, fabrication progress, material receipts, material storage and location, material withdrawal requests, material pick and issue lists" (Dharmapalan and O'Brien, 2018).…”
Section: Information Sharing In Constructionmentioning
confidence: 99%
“…The SCV of materials in industrial construction projects is reported to be low (Dharmapalan and O'Brien, 2018). These projects involve multiple supply chain participants who participate in varying capacities during the project's different phases (Caldas and Gupta, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The visibility of materials in the supply chain of industrial construction projects is reported to be low (Dharmapalan and O'Brien, 2018;Young et al, 2011). Two principal characteristics limit the effective exchange of information among supply chain stakeholders and thus inhibit visibility.…”
Section: Visibility Of Supply Chain Location and Materials Typementioning
confidence: 99%
“…The offsite supply chain locations studied include the manufacturing plant and offsite storage yards. Recently, Dharmapalan and O'Brien (2018) empirically investigated the commercial implementation of AMLTT in industrial projects. The application of AMLTT on the investigated projects was at onsite project laydown yard and both onsite and offsite laydown yards of fabricators.…”
Section: Visibility Of Supply Chain Location and Materials Typementioning
confidence: 99%
See 1 more Smart Citation